Raising Responsible Children: Forms of Parental Concern in Providing Character Education - Janes Sinaga; Juita Lusiana Sinambela; Dale Dompas Sompotan; Daniel Siswanto; Kingston Pandiangan; Beni Chandra Purba (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this paper is so that every parent understands their role in providing the first education before or after the child enters formal education in general. Often parents leave education problems to their teachers at school, but parents forget that education must start at home and parents are the teachers. By providing the first education at home through parents, the parents will be able to properly direct what are the goals or aspirations of the parents towards their children, both formally and in character. If parents do not neglect this, there will be many children who can be educated properly and correctly according to the expectations of the parents in the future. The research was conducted using qualitative methods by collecting data from bibliography of books and scientific journals as well as online media. It is hoped that this research can increase parental awareness in providing the first education to their children